Family Value System in Transformation: Case of Bosnia and Herzegovina - Košarac, Biserka; Kurteš, Ognjen (Italian Sociological Review, 2021)
Using the data of empirical research of gender roles in family carried out in 2018, the authors of this paper point out the transformation of family value system in Bosnia and Herzegovina. Postsocialist transformation in Bosnia and Herzegovina has influenced changes of value family patterns and orientations, so traditional value orientations are dominant, marked by immense value gap, instead of modernist value orientations. The results indicate that the data subjects’ answers are still traditional and patriarchal and that young men and women show tendency towards modern value orientations. The acceptance of modern attitudes is moderate and not resolute, and regarding various issues there is a large percent of irresolute answers. It can be concluded that there is certain division of values. On one side there are generations of young and women and on the other side there are generations of older and men who are very close to traditional values.